THE EFFECT OF IMAGERY AND SELF-TALK TRAINING WITH SINGLE TARGET AND TARGET TRAINING IS HINDERED ON INCREASING THE SHOOTING ACCURACY OF A DISTANCE OF 7 METERS IN PETANQUE AT THE EAST JAVA PUSLATDA - Ika Ana, Kholifatul; Nurkholis; Siantoro, Gigih; Zulfikar Rizki, Ainun (Gladi : Jurnal Ilmu Keolahragaan, 2024)
The purpose of this study is to determine the influence of the application of imagery training during shooting exercises at a distance of 7 meters with single targets and targets unable at PUSLATDA JATIM, knowing the influence with the application of self-talk exercises during shooting exercisesa distance of 7 meters with a single target and an obstacle target at PUSLATDA JATIM, Knowing the mental differences of PUSLATDA JATIM athletes after receiving mental imagery and self-talk training. This research is an experimental study. The result of this study is that there is a significant effect of imagery training on the results of single target shooting and obstacle target shooting. There is a significant effect of self-talk training on the results of single target shooting and obstacle target shooting. This research requires further research on shooting practice , especially single target shooting practice and target shooting with different sample and population conditions. As in Exercise, imagery and self-talk can be used in certain sports in athletes or sports organizations to improve ability or accuracy..